2015
DOI: 10.1080/17550874.2015.1074626
|View full text |Cite
|
Sign up to set email alerts
|

Flower colour variation in the montane plantGentiana luteaL. (Gentianaceae) is unrelated to abiotic factors

Abstract: Background: Flower colour variation among populations may result from the spatial variation of selective agents. The structure of phenotypic variation informs on the ecological processes related to this variation. Variation in floral traits is mainly attributed to variation in the pollinator fauna, while variation in vegetative traits is usually linked to abiotic factors or herbivores. Aims: We investigated the geographical variation of flower colour (and correlated traits) in Gentiana lutea and the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Conversely, the distribution of colour morphs of Gentiana lutea was unrelated to abiotic factors such as elevation, temperature, rainfall or radiation (Veiga et al . ).…”
Section: Evolutionary Mechanisms To Maintain Flower Colour Polymorphimentioning
confidence: 97%
“…Conversely, the distribution of colour morphs of Gentiana lutea was unrelated to abiotic factors such as elevation, temperature, rainfall or radiation (Veiga et al . ).…”
Section: Evolutionary Mechanisms To Maintain Flower Colour Polymorphimentioning
confidence: 97%
“…Previous studies have investigated ecological interactions in the same populations (Rossi et al , ) and karyological features of the studied subspecies (Rossi et al ). Recently, several authors have studied the occurrence of different colour morphs in Spanish populations of G. lutea , and they found that pollinators and predators, but not abiotic factors, act as selective agents on flower colours (Sobral et al , Veiga et al , ). However, we did not encounter plants with different floral phenotypes in our study populations.…”
Section: Methodsmentioning
confidence: 99%
“…The pollinator assemblages are made up mostly of bumblebee species (Veiga et al, 2015;Sobral et al, 2015). Previous studies conclude that: (i) Gentiana lutea flower color variation does not result from adaptation to environmental factors, such as elevation, temperature, radiation, and precipitation (Veiga et al, 2016)…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%